C-type lectin-like receptor 2 expression is decreased upon platelet activation and is lower in most tumor entities compared to healthy controls - Etemad, Mani; Christodoulou, Foteini; Uhlig, Stefanie; Hassel, Jessica C.; Schrotz-King, Petra; Brenner, Hermann; Ulrich, Cornelia; Bieback, Karen; Klüter, Harald; Bugert, Peter (Cancers, 2023)
The C-type lectin-like receptor 2 (CLEC-2) is expressed on platelets and mediates binding to podoplanin (PDPN) on various cell types. The binding to circulating tumor cells (CTCs) leads to platelet activation and promotes metastatic spread. An increased level of soluble CLEC-2 (sCLEC-2), presumably released from activated platelets, was shown in patients with thromboinflammatory and malignant disease. However, the functional role of sCLEC-2 and the mechanism of sCLEC-2 release are not known. In this study, we focused on the effect of platelet activation on CLEC-2 expression and the sCLEC-2 plasma level in patients with cancer. First, citrated blood from healthy volunteer donors (n = 20) was used to measure the effect of platelet stimulation by classical agonists and PDPN on aggregation, CLEC-2 expression on platelets with flow cytometry, sCLEC-2 release to the plasma with ELISA and total CLEC-2 expression with Western blot analysis. Second, sCLEC-2 was determined in plasma samples from healthy donors (285) and patients with colorectal carcinoma (CRC; 194), melanoma (160), breast cancer (BC; 99) or glioblastoma (49). PDPN caused a significant increase in the aggregation response induced by classical agonists. ADP or PDPN stimulation of platelets caused a significant decrease in CLEC-2 on platelets and sCLEC-2 in the plasma, whereas total CLEC-2 in platelet lysates remained the same. Thus, the increased plasma level of sCLEC-2 is not a suitable biomarker of platelet activation. In patients with CRC (median 0.9 ng/mL), melanoma (0.9 ng/mL) or BC (0.7 ng/mL), we found significantly lower sCLEC-2 levels (p < 0.0001), whereas patients with glioblastoma displayed higher levels (2.6 ng/mL; p = 0.0233) compared to healthy controls (2.1 ng/mL). The low sCLEC-2 plasma level observed in most of the tumor entities of our study presumably results from the internalization of sCLEC-2 by activated platelets or binding of sCLEC-2 to CTCs.
Gesehen am 30.01.2024